Impact of income on the structure of alcohol sales in Russia - YE Razvodovsky (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2021)
Significant changes in the structure of alcohol consumption, as well as changing economic cycles, make Russia a convenient object for studying the impact of the population's income on the structure of alcohol consumption. The aim of this study was to study the relationship between income and the structure of alcohol sales in Russia at the population level.  Methods: A comparative analysis of the dynamics of the gross domestic product (GDP) and the level of sales of various types of alcoholic beverages/the structure of alcohol sales in Russia in the period from 1990 to 2015 was carried out. Statistical data processing was carried out using the STATISTICA 10 package.  Results: According to the results of the correlation analysis, GDP is negatively correlated with the sale of vodka (r = -0.63; p <0.000)/the share of vodka in the sales structure (r = -0.8; p <0.000) and positively correlates with beer sales (r = 0.5; p <0.000)/share of beer in the sales structure (r = -0.72; p <0.000), as well as with wine sales (r = 0.73 ; p <0.000)/share of wine in the sales structure (r = 0.67; p <0.000).  Conclusions: The improvement of the macroeconomic situation and the growth of incomes of the population was one of the drivers of the change in the structure of alcohol consumption in Russia in favor of low-alcohol drinks.